An AHP-based evaluation method for teacher training workshop on information and communication technology - Lucas, Rochelle Irene (Animo Repository, 2017)
The emergence of information and communication technology (ICT) has created opportunities for enhancing the learning process at different educational levels. However, its potential benefits can only be fully realized if teachers are properly trained to utilize such tools. The rapid evolution of ICT also necessitates rigorous assessment of training programs by participants. Thus, this study proposes an evaluation framework based on the Analytic Hierarchy Process (AHP) to systematically evaluate such workshops designed for teachers. The evaluation model is decomposed hierarchically into four main criteria namely: (1) workshop design, (2) quality of content of the workshop, (3) quality of delivery of the content of the workshop, and the (4) relevance of the workshop. These criteria are further disaggregated into 24 sub-indicators to measure the effectiveness of the workshop as perceived by the participants based on their own expectations. This framework is applied to a case study of ICT workshops done in the Philippines. In this case, relevance of the workshop is found to be the most important main criterion identified by the participants, particularly on the new ICT knowledge that promotes teachers’ professional growth and development. The workshop evaluation index (WEI) is also proposed as a metric to support decision-making by providing a mechanism for benchmarking performance, tracking improvement over time, and developing strategies for the design and improvement of training programs or workshops on ICT for teachers. © 2017 Elsevier Ltd